Ubiquitin-like proteins NEDD8 and SUMO2 control epithelial homeostasis, regeneration, and inflammation - Mårten C. G. Winge; Leandra V. Jackrazi; Douglas F. Porter; Suhas Srinivasan; Vanessa Lopez-Pajares; Dayan J. Li; Benjamin Pham; Aubrey Houser; Spencer H. Cha; Robin M. Meyers; Lisa A. Ko; Luca Ducoli; et al. (Science, 2026)
Stratified epithelial differentiation involves transcriptional and proteomic remodeling. Here, multiomic profiling implicated ubiquitin and related posttranslational networks in differentiation dynamics. Systematic perturbation of ubiquitin-like machinery in primary human keratinocytes which uncovered opposite functions of neural-precursor-cell–expressed, developmentally down-regulated 8 (NEDD8) and small ubiquitin-related modifier 2 (SUMO2). Generation of conditional knockout mice established essential roles for NEDD8 in progenitor maintenance, skin regeneration, and inflammation, whereas SUMO2 was required for differentiation. Beyond ubiquitin-proteasome-concordant changes, NEDD8 directed proteomic regulation correlated with RNA abundance. Integration of immunoprecipitation– mass spectrometry with genome-wide suppressor screening revealed context-specific NEDDylation dependencies. Among effectors, heterogeneous nuclear ribonucleoprotein U (HNRNPU) emerged as a posttranscriptional regulator of epithelial cell state whose RNA binding repertoire was modulated by NEDDylation. Thus, NEDD8 and SUMO2 play opposite roles in epithelial homeostasis, regeneration, and inflammation, demonstrating multiple ways ubiquitin-like networks govern tissue homeostasis.